The flagria group of Keilbachia Mohrig (Diptera, Sciaridae) in a biodiversity hot spot: nine new sympatric species from Kambaiti, Myanmar - Hippa, Heikki; Vilkamaa, Pekka (Zootaxa, 2007)
The Keilbachia flagria group is defined for the species bearing two or more mesial megasetae arising from a common basal body on the gonostylus. Nine new species are described from Kambaiti, Myanmar (Burma): K. acamptochaeta, K. bicuspis, K. fasciata, K. filigera, K. flabellata, K. foveolata, K. gigas, K. oligonema and K. rima. Three additional new species were seen in the material from Kambaiti but were left unnamed because of the poor condition of the specimens. The total number of named sympatric Keilbachia species in Kambaiti is now 18.